Edukasi Kesehatan Tentang Cuci Tangan Pakai Sabun (CTPS) dengan Media Komik pada Siswa SD di Kabupaten Tana Toraja - Yosinta Yosinta; Suriah Suriah; Muh Rachmat (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Hand washing has proven to be the most important step in avoiding disease and preventing the spread of germs to others. School-age children are a critical age group because at that age a child is vulnerable to health problems. As time goes by, comic media can also be used in health education. This study aims to determine differences in knowledge, attitudes, and actions of elementary school students towards CTPS before and after education with comic media. This research is a quantitative research that uses a quasi experimental design with the design of the Nonequivalent Control Group. The population in this study were the fourth and fifth grade students in 216 Tetebassi Elementary School, Talluborongna 110 Elementary School, 117 Rorre Elementary School, 107 Rante Lemo Elementary School, North Makale District, 541 students with 134 sample. Purposive sampling technique for determining samples. Measuring tool for this research is questionnaire. The results of this study found that there were differences in CTPS before and after intervention in the intervention group and the control group with knowledge (p=0.004), attitudes (p=0.043) and actions (p=0.001). In this study there are differences in knowledge of CTPS before and after intervention in the intervention group and the control group in students in Makale Utara Subdistrict, Tana Toraja District. For the next researcher, to conduct an educational media trial before being used on the target of school children.